Establishment of metrological parameters of the method for measuring the protein mass fraction in fish food products by the Kjeldahl method - A. V. Kozin; L. S. Abramova; E. S. Guseva; I. V. Derunets (Пищевые системы)
In laboratory practice, there are many protein quantification methods, and all of them have their own advantages and disadvantages. The most common and widely used method for the protein analysis in food products, including fish, is the Kjeldahl method. However, the current standards for measurement methods for the determination of the protein content in fish food products do not provide for the use of devices that meet the modern level of technical development, and also do not contain metrological indicators that guarantee the reliability of the results obtained. The aim of the study was to substantiate the method for measuring the protein mass fraction in fish food products by the Kjeldahl method on an automatic analyzer and to establish metrological parameters. The assessment of the quality indicators of the Kjeldahl measuring method was carried out using a Kjeltec System 2300 Nitrogen Analyzer (Foss Analytical AB, Sweden) in the form of a characteristic of the measurement error and its components, which will provide results with the required accuracy.